TRIM28 variants and Wilms' tumour predisposition - Hol, Janna A; Diets, Illja J; Krijger, Ronald R; Heuvel‐Eibrink, Marry M; Jongmans, Marjolijn CJ; Kuiper, Roland P (The Journal of pathology, 2021)
TRIM28 was recently identified as a Wilms' tumour (WT) predisposition gene, with germline pathogenic variants identified in around 1% of isolated and 8% of familial WT cases. TRIM28 variants are associated with epithelial WT, but the presence of other tumour components or anaplasia does not exclude the presence of a germline or somatic TRIM28 variant. In children with WT, TRIM28 acts as a classical tumour suppressor gene, with both alleles generally disrupted in the tumour. Therefore, loss of TRIM28 (KAP1/TIF1beta) protein expression in tumour tissue by immunohistochemistry is an effective strategy to identify patients carrying pathogenic TRIM28 variants. TRIM28 is a ubiquitously expressed corepressor that binds transcription factors in a context‐, species‐, and cell‐type‐specific manner to control the expression of genes and transposable elements during embryogenesis and cellular differentiation. In this review, we describe the inheritance patterns, histopathological and clinical features of TRIM28‐associated WT, as well as potential underlying mechanisms of tumourigenesis during embryonic kidney development. Recognizing germline TRIM28 variants in patients with WT can enable counselling, genetic testing, and potential early detection of WT in other children in the family. A further exploration of TRIM28‐associated WT will help to unravel the diverse and complex mechanisms underlying WT development. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.